When stars are scattered - Jamieson, Victoria; Mohamed, Omar (Social worker) (Dial Books for Young Readers, 2020)
"Omar and his younger brother Hassan live in a refugee camp, and when an opportunity for Omar to get an education comes along, he must decide between going to school every day or caring for his nonverbal brother in this intimate and touching portrayal of family and daily life in a refugee camp"--